Effect of Cash Turnover, Receivable Turnover and Inventory Turnover on Return on Investment (ROI) at PT. Kimia Farma Tbk - Hermayani, Regitha Aulia; Sumawidjaja, Riyandi Nur (International Journal of Community Service & Engagement, 2025)
This study examines the effect of cash, accounts receivable, and inventory turnover on return on investment at PT Kimia Farma Tbk for 2019-2023. The data in the study are secondary data sourced from financial data on the Kimia Farma Website. Statistical analysis techniques include regression testing, correlation, determination, and hypothesis testing. The results showed that Cash Turnover positively and significantly affected Return On Investment. In contrast, Receivables Turnover and Inventory Turnover negatively and significantly affected Return On Investment. Overall, the three ratios are positive and significant to the Return On Investment of PT Kimia Farma Tbk in that period